2008
DOI: 10.1002/j.0022-0337.2008.72.11.tb04613.x
|View full text |Cite
|
Sign up to set email alerts
|

A Model for an Integrated Predoctoral Implant Curriculum: Implementation and Outcomes

Abstract: The implementation of an implant dental curriculum in U.S. dental schools has been consistently increasing from 33 percent in 1974 to 97 percent in 2004. Among these, only 51 percent have clinical components implemented. A survey of students conducted in 2004 at New York University College of Dentistry (NYUCD) showed an inadequacy in clinical implant restoration experience by graduation. This prompted the development of an extensive dental implant curriculum at NYUCD to meet the needs of the dental students. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
35
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…Results from this study indicate that dental students can provide good results with meaningful impact on patients’ lives. Patients have sought care at dental institutions for implant treatment because they typically offer low‐cost programs for surrounding communities and underserved populations . This study also indicated that predoctoral students provided STI therapy that met the patient satisfaction.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Results from this study indicate that dental students can provide good results with meaningful impact on patients’ lives. Patients have sought care at dental institutions for implant treatment because they typically offer low‐cost programs for surrounding communities and underserved populations . This study also indicated that predoctoral students provided STI therapy that met the patient satisfaction.…”
Section: Discussionmentioning
confidence: 74%
“…Improvement in comfort with eating, esthetics, phonetics, and overall satisfaction is well‐documented with STI therapy . By having well‐defined and stringent patient selection criteria, implant educational programs can select the patients most suitable for predoctoral treatment and can provide successful comprehensive therapy. With increasing financial burdens in society, patients seeking implant care at dental institutions as an alternative to private practice can be anticipated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the preparation of clinical materials in the laboratory (e.g., the fabrication of drill templates) and clinical implant planning received very positive feedback from the undergraduate students, and these activities had a positive influence on the graduates' future plans to perform implant therapy [4,23,24]. However, Fortes et al [25] reported that implant planning by novice and experienced dentists differed if standard radiographs were used instead of CBCT images.…”
Section: Implant Planning By Undergraduatesmentioning
confidence: 99%
“…Therefore, a close examination of current implant education for dental students is important to identify challenges and propose solutions for further curriculum improvement. Many studies have been published on predoctoral implant education in North American dental schools 7 , 8 , 10 , 12 , 18 20 . However, only one of those assessed implant education that included preclinical laboratory exercises 10 …”
mentioning
confidence: 99%